2021
DOI: 10.3389/fphar.2021.623985
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelic Communitas: Intersubjective Experience During Psychedelic Group Sessions Predicts Enduring Changes in Psychological Wellbeing and Social Connectedness

Abstract: Background: Recent years have seen a resurgence of research on the potential of psychedelic substances to treat addictive and mood disorders. Historically and contemporarily, psychedelic studies have emphasized the importance of contextual elements ('set and setting') in modulating acute drug effects, and ultimately, influencing long-term outcomes. Nevertheless, current small-scale clinical and laboratory studies have tended to bypass a ubiquitous contextual feature of naturalistic psychedelic use: its social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
121
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 147 publications
1
121
2
1
Order By: Relevance
“…Automatic email reminders were then sent out at multiple time-points at baseline (one week before the experience), one day after the experience and 4 weeks after the indicated date of the experience to participants who signalled consent, including links to surveys hosted on the online platform SurveyGizmo. All methods were carried out by relevant guidelines and regulations (see Kettner et al79 for details).Survey findings were complemented by results from controlled a controlled clinical-trial comparing psilocybin versus escitalopram treatment for major depression. The data from 59 participants with major depression (>17 on Hamilton-Depression [HAM-D-17] scale at screening) who completed the trial was used (30 participants for psilocybin and 29 for escitalopram).…”
mentioning
confidence: 99%
“…Automatic email reminders were then sent out at multiple time-points at baseline (one week before the experience), one day after the experience and 4 weeks after the indicated date of the experience to participants who signalled consent, including links to surveys hosted on the online platform SurveyGizmo. All methods were carried out by relevant guidelines and regulations (see Kettner et al79 for details).Survey findings were complemented by results from controlled a controlled clinical-trial comparing psilocybin versus escitalopram treatment for major depression. The data from 59 participants with major depression (>17 on Hamilton-Depression [HAM-D-17] scale at screening) who completed the trial was used (30 participants for psilocybin and 29 for escitalopram).…”
mentioning
confidence: 99%
“…Classic psychedelics are a family of drugs whose central mode of action is through the 2A receptor of the serotonergic system (Nichols, 2016). Their effect is known to be context-dependent Hartogsohn, 2017;Hartogsohn, 2020), and they are known to produce a myriad of intense experiences (Harner, 1973;Grof, 1975Grof, /2016Shanon, 2002), including so-called mystical-type and ego-dissolution experiences (Pahnke and Richards, 1966;Griffiths et al, 2008;Nour et al, 2016), emotional breakthrough, release or catharsis and psychological processing of traumatic events (Frederking, 1955;Riba et al, 2006;Gasser et al, 2014;Belser et al, 2017;Roseman et al, 2019), challenging high-anxiety experiences (Carbonaro et al, 2016), prophetic-type experiences (Strassman, 2014), visionary and hallucinatory experiences (Knauer and Maloney, 1913;Klüver, 1926;Reichel-Dolmatoff, 1975;Luna andAmaringo, 1991/1999;Shanon, 2002;Roseman, 2019), and experiences of social connection (Dolder et al, 2016;Pokorny et al, 2017;Apud, 2020b;Forstmann et al, 2020;Kettner et al, 2021). The context-dependent quality of psychedelics has led them to be referred as 'non-specific amplifiers' (Grof, 1975(Grof, / 2016)meaning they intensify whatever is in the vicinity of the experiencer, whether good or bad or intrinsically (e.g., in their own mind) or extrinsically located (i.e., in their immediate environment).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in addition to the above personal experiences, there are important participatory and relational elements in ayahuasca ceremonies that deserve greater attention from researchers. Several studies have reported psychedelic induced group emotional synchrony, communitas, or other relational processes, whether in rituals (La Barre, 1938Barre, /1975Gearin, 2016a;Kettner et al, 2021), festivals (Saldanha, 2007;St John, 2009;Winkelman, 2015;Forstmann et al, 2020), or group therapy (Trope et al, 2019). Within some indigenous shamanic traditions, healing is pursued through the relational act of singing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, a statistical correlation was calculated between responses on standard psychological and health questionnaires among participants of different ayahuasca denominations. Kettner et al ( 2021 ) developed and investigated the psychometric properties of a short instrument—eight items—to assess what the authors have called Intersubjective Experience During Psychedelic Group Sessions, evaluating how participants of ayahuasca rituals related to each other during sessions and established social bonds among themselves. However, as the ayahuasca consumption setting is complex and involves other domains in addition to these, the development of more instruments is necessary.…”
Section: Introductionmentioning
confidence: 99%